Generation of knock‐in mice that express nuclear enhanced green fluorescent protein and tamoxifen‐inducible Cre recombinase in the notochord from Foxa2 and T loci. Issue 3 (25th February 2013) - Imuta, Yu; Kiyonari, Hiroshi; Jang, Chuan‐Wei; Behringer, Richard R.; Sasaki, Hiroshi
Summary The node and the notochord are important embryonic signaling centers that control embryonic pattern formation. Notochord progenitor cells present in the node and later in the posterior end of the notochord move anteriorly to generate the notochord. To understand the dynamics of cell movement during notochord development and the molecular mechanisms controlling this event, analyses of cell movements using time‐lapse imaging and conditional manipulation of gene activities are required. To achieve this goal, we generated two knock‐in mouse lines that simultaneously express nuclear enhanced green fluorescent protein (EGFP) and tamoxifen‐inducible Cre, CreERT2, from two notochord gene loci, Foxa2 and T (Brachury). In Foxa2nEGFP‐CreERT2/+ and TnEGFP‐CreERT2/+ embryos, nuclei of the Foxa2 or T‐expressing cells, which include the node, notochord, and endoderm (Foxa2) or wide range of posterior mesoderm (T), were labeled with EGFP at intensities that can be used for live imaging. Cre activity was also induced in cells expressing Foxa2 and T 1 day after tamoxifen administration. These mice are expected to be useful tools for analyzing the mechanisms of notochord development. genesis 51:210–218, 2013. © 2013 Wiley Periodicals, Inc.